The Role of Inflammation in the Pathogenesis of Macular Edema Secondary to Retinal Vascular Diseases - Francisco J. Ascaso; Valentín Huerva; Andrzej Grzybowski (Mediators of Inflammation)
Macular edema (ME) is a nonspecific sign of numerous retinal vascular diseases. This paper is an updated overview about the role of inflammatory processes in the genesis of both diabetic macular edema (DME) and ME secondary to retinal vein occlusion (RVO). We focus on the inflammatory mediators implicated, the effect of the different intravitreal therapies, the recruitment of leukocytes mediated by adhesion molecules, and the role of retinal Müller glial (RMG) cells.